Converting Small and Medium Sized Enterprise (SME) Contractor to Industrialised Building System (IBS) Installer - Selamat, Md Fuad; Jabar, Izatul laili; Kaliwon, Julaida (Research in Management of Technology and Business, 2022)
Conventional construction may be impeded by lack of trained labour, inclement weather, quality issues, inadequate site circumstances, time consuming and many more. Previous study has proved that the adoption of Industrialized Building System (IBS) offers the benefits in terms of speed, safety and quality as compared to conventional construction. Government has taken numerous measures to ensure the successful implementation of IBS through Construction Industry Development Board (CIDB), among others is conducting training programs such as IBS installer training programme. However, there are still many small and medium sized enterprise (SME) contractors are apprehensive about implementing the IBS system and prefer to stick with the traditional construction method. Therefore, this paper aims to propose the suitable strategies for converting SME contractors into IBS installer. The research objective is to identify the challenges in converting the SME contractors into IBS installer and to propose strategies for converting SME contractors into IBS installer. The quantitative data was collected using questionnaire and distributed to the contractors of IBS construction project. This research identified the current contractor’s challenges and recommendation in improving strategies for converting SME contractors into IBS installer.